Multimodal moves in the "About Us" section of Malaysian private hospitals’ websites - Nasser Salimi Aghbolagh,; Wan Fatimah Solihah Wan Abdul Halim, (Penerbit Universiti Kebangsaan Malaysia, 2025)
The "About Us" sections of private hospital websites are essential for establishing credibility, highlighting unique offerings, and building trust with potential local and international patients. These sections are crucial in promoting private hospitals and contributing to the growth of the medical tourism industry. However, limited research has explored the effectiveness of this promotional channel, particularly from a multimodal perspective. Limited prior studies have examined the generic structure of this section by integrating multimodal discourse analysis. This study employs a multimodal move analysis framework to examine the "About Us" sections of 41 Malaysian private hospital websites, with "move" as distinct strategies or steps that collectively develop rhetorical strategies to fulfill specific communicative purposes. The methodology includes two phases: verbal move analysis, guided by Swales’ genre analysis framework, to identify rhetorical moves expressed through text, and visual move analysis, based on Kress and van Leeuwen’s Visual Grammar Theory, to explore representational, interactive, and compositional meanings of visual elements. The findings reveal how verbal and visual elements interact to achieve cohesive communicative goals. Verbal components emphasize credibility, professionalism, and technological advancements, while visuals such as images, diagrams, and banners evoke trust, engagement, and emotional resonance. Moves like "Establishing Credentials" and "Indicating Value of the Hospital" are achieved through a combination of text and visuals, creating cohesive representations. This study provides insights into how private hospitals can leverage multimodal strategies to promote their services and attract international medical tourists and collaborators effectively.